Reviews. Issue 1 (1st April 2018) - Lin, Yu-Han; Berndt, Jaqueline; Reisel, Mary
Identity Politics and Popular Culture in Taiwan: A Sajiao Generation, HSIN-I Sydney Yueh (2016) 1st ed., Lexington Books, 222 pp., ISBN: 9781498510325, Hardback, 85.00 (£54.95); ISBN: 9781498510332, eBook, 80.50 (£54.95)Rewriting History in Manga: Stories for the Nation, Nissim Otmazgin and Rebecca Suter (EDS) (2016) 1st ed., New York: Palgrave Macmillan, 208 pp., ISBN: 9781137554789, h/bk, 99.99; ISBN: 9781137551436, electronic, 79.99Idols and Celebrity in Japanese Media Culture, Patrick W. Galbraith and Jason Karlin (EDS) (2012) 1st ed., New York: Palgrave Macmillan, 239 pp., ISBN: 9780230298309, h/bk, 100, 00; ISBN: 9781349334452, p/bk, 95, 00; Electronic ISBN: 9781137283788, 79, 99